THE POPULAR FESTIVALS: PRACTICES OF URBAN LIFESTYLE - Costa, Carmem Lúcia (Revista Cidades, 2021)
This article is the product of a doctoral thesis helded at the University of São Paulo and defended in 2010 where we researched the commodification of popular festivals, specifically the Party in Honor of Our Lady of the Rosary in the Catalão city of the interior of Goiás in the process of commodification identified as the reproduction of the urban place to capture festive practices spectacularizing them and then inserting them into the logic of the consumer / city. Thus the understanding of the urban planning and everyday life for the realization of the goods is essential.